O kulturowym dziedzictwie wypasania owiec i symbolice pasterskiej oraz o kunszcie kucharskim i dobrym smaku - Rembierz, Marek (Studia Etnologiczne i Antropologiczne, 2014)
A great culture-creating event “The Carpathian Sheep Graze — Transhumance 2013”, organized with due respect for pastoral tradition, and “Lamb Meat Feast” in Ustroń are examples of restitution and popularization of the cultural heritage of sheep farming and pastoral symbolics. Both events appeal to very deep layers of tradition, which raise reflection on culture-creating aspects of sheep farming (one of the oldest forms of agricultural economy), on the signs of pastoral customs and symbolics, and on culinary traditions. Pastoral elements still seem to be present in modern culture, especially in the religious symbolic imagination. However, most frequently there is no direct presence of sheep and shepherds, which might make them only a “relic” of the past.